A Novel Resveratrol Analog Upregulates SIRT1 Expression and Ameliorates Neointima Formation - Yuan, Baohui; Liu, He; Dong, Xiaoliang; Pan, Xiaohua; Sun, Xun; Sun, Jia; Pan, Li-Long (Frontiers in Cardiovascular Medicine, 2021)
Neointima formation is a serious complication caused by mechanical trauma to the vessel. (R)-4,6-dimethoxy-3-(4-methoxy phenyl)-2,3-dihydro-1H-indanone [(R)-TML 104] is a synthesized analog of the natural product resveratrol sesquiterpenes (±)-isopaucifloral F. The present study aimed to investigate the effects and underlying mechanisms of (R)-TML104 on neointima formation. Our results showed that (R)-TML104 prevented neointima formation based on a carotid artery injury model in mice. Furthermore, (R)-TML104 inhibited platelet-derived growth factor-BB (PDGF-BB)-induced vascular smooth muscle cells (VSMC) phenotypic transformation, evidenced by increased α-smooth muscle actin, reduced VSMC proliferation, and migration. Simultaneously, (R)-TML104 upregulated sirtuin-1 (SIRT1) expression in VSMC. We further uncovered that SIRT1 expression is critical for the inhibitory effects of (R)-TML104 on PDGF-BB-induced VSMC phenotypic transformation in vitro and injury-induced neointima formation in vivo. Finally, (R)-TML104-upregulated SIRT1 inhibited PDGF-BB-induced VSMC phenotypic transformation by downregulating nicotinamide adenine dinucleotide phosphate oxidase 4 expression via decreasing nuclear factor-κB acetylation. Taken together, these results revealed that (R)-TML104 upregulates SIRT1 expression and ameliorates neointima formation. Therefore, the application of (R)-TML104 may constitute an effective strategy to ameliorate neointima formation.